The sustainability challenges in the adoption of cleaner production system: a review - Yusup, Mohd Zaki; Wan Mahmood, Wan Hasrulnizzam; Salleh, Mohd Rizal; Muhamad, Mohd Razali (2014)
The adoption of cleaner production systems potentially reduces the risk of hazard in work environments, improves the environmental management performance as well as streamlining the sustainability in manufacturing operations. However, failure to identify and understand the challenges in implementing this practice may cause the implementation process becomes less efficient. The literatures showed that the requirement to balance four key challenges, namely economic performance, legislation compliance, psychological concern and social responsiveness can enhance the adaptation process of cleaner production system. The ability to detect and understanding every challenge identified is very crucial, primarily to set better focus and strategic planning on getting the optimum benefits, as well as improve the environmental performance in revolutionising sustainable manufacturing practice.